Perencanaan Sistem Pengelolaan Sampah Di PT PLN (Persero) Unit Pendidikan Dan Pelatihan - Randy Zulkarnain; Robby Fiqry Maulana; Netti Herlina; Lies Setyowati (KILAT, 2020)
The source of waste produced by PT PLN (Persero) UPDL Tuntungan comes from offices and classrooms, mess and dormitories, parks and roads as well as dining rooms. We need a good waste management system planning for optimisation existing waste treatment. The research objective is to calculate the generation and composition, plan operational techniques and waste management schemes. The method of measuring the generation and composition of waste uses SNI 19-3964-1994. The results of the study showed that the solid waste generation based on the maximum capacity produced was 210.10 kg/day or 1,752.23 l/day with the composition of the solid waste produced as a whole of food remaining 11.20%, wood and plant waste 65.07%, fabric/textile 1.59%, rubber 1.26%, plastic 10.80%, metal 0.75%, glass, 1.14%, paper 5.34%, tissue 1.29%, and styrofoam 1, 56%. Garbage operational techniques that will be planned starting from storage using a 20L bin will be divided into 5 types, namely organic, plastic, paper, etc. and hazardous and toxic materials, and placed 1 container of 120L size garbage for trash from the dining room. Collection and transfer using 660L depot transfer. Transporting garbage using a 1 m3 garbage motor to the TPS for further composting and sorting. For garbage that still has a sale value, it is sold to pelapak and the residual waste is taken to the landfill.